Implementing clustering technique in writing descriptive texts - Husniah Husniah; Burhanuddin Yasin; Siti Sarah Fitriani (English Education Journal, 2021)
This experimental research was conducted to find out the effect of using clustering technique on the students’ writing skills at Senior High School No. 1 Delima, Pidie District. It also has several sub-focuses, namely figuring out the students’ writing content, organization, and language use. The subjects of the study were the 10th grade students that were divided in random sampling into the experimental and the control groups. This procedure was carried out through homogeneity of the selected samples. To expose the focuses of answers, the pretest and post-test instruments were applied to both groups. The result showed that the students in experimental group had an improved quality of writing a descriptive text than that of the control-group students.  At a level of significance 0.05, the ttestscore was higher than ttablescore (8,441,684). In addition, the mean score of the experimental group (78,79) was higher than the mean score of the control group (53,75). This figure has corresponded with the results of the three writing aspects of the students’ work, which also brought a relatively positive achievement. This means that there were significant improvements regarding the students’ writing aspects of content, organization, and language use in descriptive texts respectively.